THE PLACE OF HUMAN RESOURCES IN THE HOTEL AND RESTAURANT BUSINESS IN THE INTEGRATION AND GLOBALIZATION CONDITIONS - Balatska, Natalia; Kalienik , Kseniia; Skrynnik , Viktoriia (Socio-economic relations in the digital society, 2022)
The aim of the article is to analyze and characterize the intellectual potential of the labor resources of the enterprise and its role in improving the efficiency of business management in hotels and catering establishments. Based on the methods of scientific logic, general concepts are formulated and their role in the system of categorical apparatus is reflected. The systematic approach helped to determine the role of human resources in the hotel and restaurant business, which perform certain functions, and between which there is a relationship (structure) that determines the position of each element (person) in the overall service system.It is substantiated that hotel employees are an important part of the final product, so the quality of hotel and catering services depends on the qualifications and awareness of employees. Therefore, effective personnel management has become one of the most important functions in the hotel and restaurant business. The article considers the features of employment and personnel management in the field of hospitality and catering. The structural relationships, functional responsibilities and capabilities of managers and employees are defined. The steps of management in achieving marketing goals are staged. The need to improve personnel management was confirmed. The concept of “intellectual work” was introduced. It is substantiated that not only the principles and methods of hotel and restaurant management have undergone serious changes, but also the methods of customer service have become high-tech and consumer-oriented. The high culture of service and competitiveness of the hotel and catering industry is organically linked to the highly professional training and technical literacy of workers in this industry. The direction and modern possibilities of hotel and restaurant business development are determined, among the main ones: development of small hotel business networks; deepening restaurant specialization; introduction of new computer technologies; development of international hotel and restaurant chains and, of course, improving the quality of staff.
Keywords: personnel; hotel and restaurant business; management; human resources; globalization; working conditions